Maqashid Syariah dalam Perlindungan Hukum terhadap Korban Prostitusi Online di Jawa Tengah - Subeno, Handoyo; Surbakti, Natangsa; Iksan, Muchamad (Al-Qisthu, 2024)
This study delves into the legal protection afforded to women who are This study investigates the legal protection aspects for women victims of online prostitution and the Islamic legal perspective on such cases. The research employs a mixed-methods approach, combining legislative analysis and case studies from the PPA Unit of Subdirectorate IV/Renakta, Ditreskrimum, Central Java Police. The study reveals a need for legal certainty in protecting women victims of online prostitution, as current criminal laws do not target the users of such services. Existing legal instruments only address pimps and commercial sex workers. Legal protection is formulated through regulations and sanctions, including preventive and repressive approaches. Challenges include limited compliance by perpetrators, insufficient attention from law enforcement officers, and a lack of investigative knowledge in handling these cases. Proposed solutions encompass restitution, rehabilitation, repatriation, and social reintegration. From an Islamic legal perspective, victim protection refers to the concept of restitution, as articulated through diat and al-gharamah al-maaliyah.